Exploring the availability of specialist health workforce education in East and Southern Africa: a document analysis. (1st July 2022) - Asamani, James Avoka; Christmals, Christmal Dela; Nyoni, Champion N; Nabyonga-Orem, Juliet; Nyoni, Jennifer; Okoroafor, Sunny C; Ahmat, Adam
Abstract : Background: Specialist health professionals improve health outcomes. Most low-income and middle-income countries do not have the capacity to educate and retain all types of specialists across various health professions. This study sought to explore and describe the opportunities available for specialist health professions education and the pathways to becoming a specialist health professional in East and Southern Africa (ESA). Understanding the regional capacity for specialist education provides opportunities for countries to apply transnational education models to create prospects for specialist education. Methods: A document analysis on specialist training programmes for health professionals was conducted in twenty countries in ESA to establish the capacity of specialist education for health professionals. Data were collected from policy documents, grey literature and websites at the country and institution levels. Findings: We found 288 specialist health professions education programmes across ten professional categories in 157 health professions education institutions from 18 countries in the ESA are reported. Medical and Nursing specialist programmes dominate the list of available specialist programmes in the region, while Kenya, South Africa and Ethiopia have the highest number of specialist programmes. Most included specialist programmes were offered at the Master's level or as postgraduate diplomas. There is a general uneven distribution of specialist health professions education programmes within the ESA region despite sharing almost similar sociogeographical context and disease patterns. Current national priorities may be antecedent to the diversity and skewed distribution of specialist health professions programmes. Conclusion: Attention must be paid to countries with limited capacity for specialist education and to professions that are severely under-represented. Establishing regional policies and platforms that nurture collaborations towards specialist health professions education may be a proximal solution for increased regional capacity for specialist education.